Mindfulness Mobile Application Menurunkan Tingkat Stres Mahasiswa : A Literature Review - Hasanah Eka Wahyu Ningsih; Meidiana Dwidiyanti; Elis Hartati (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2018)
Background: Stress among college students have been widely researched. The interventions such as mindfulness, meditation, relaxation and yoga using mobile application become most appealing choices to reduce stress. Technology is used as media to help implementing the interventions include mindfulness mobile application. It provides mindfulness steps and other features.Purpose: The aim of this paper is to evaluate previous research studies of mindfulness mobile application on decreasing stress level among college students.Method: Literature searches were conducted in October 2018. The search involved the utilization of the following online database: Google Scholar dan Medline. Keywords were “stress, mindfulness, and mobile application”. Searches were limited from 2008 to 2018 with paper in full-text and English language.Results: Four literatur were found which met inclusion and exclusion criteria. Three themes were identified: aplikasi mindfulness, framework penggunaan aplikasi, dan mengukur tingkat stres. Conclusion: This review expands the knowledge in the area of stress reduction using mindfulness mobile application and calls for further research. The researchers should develop an application using mindfulness as the therapy to decrease stress level of college students. The institution or universities should utilize the findings of this review to promote training of mindfulness in managing the stressors or reducing stress through mobile application.